Surgical Termination of Pregnancy: Evaluation of 14,903 Cases - Hale Aktun; Pinar Cakmak; Perran Moroy; Yagmur Minareci; Hakan Yalcin; Leyla Mollamahmutoglu; Nuri Danisman (Elsevier, 2006)
Objective: To evaluate the demographic and clinical characteristics of patients who underwent surgical termination of pregnancy and to assess the efficacy of the termination methods. Materials and Methods: This retrospective study was carried out on 14,903 healthy women who had intrauterine pregnancy of ≤ 10 weeks of gestation as determined by transvaginal ultrasonography. All patients underwent either suction curettage (SC) with dilatation or SC only. Family planning counseling was given to all patients before the procedure and subjects were evaluated for any complications after the procedure. Results: SC with dilatation was performed in 43.2% of patients and SC only was performed in 56.8%. Mean age was 31 ± 4.3 years. Only 5% of cases were primigravidas and 87% had formal education; 91% had one or more surgical abortions for previous pregnancies. Before the procedure, 67% were using coitus interruptus, 10% condom, 6% intrauterine device, 5% vaginal lavage, and 3% oral contraceptives as the contraceptive method, and 9% did not use any contraception. Infection, excessive bleeding, retention of fetoplacental material and uterine perforation were reported as complications of the procedure. After the procedure and following family planning counseling, 92% began to use an efficient, modern contraceptive method. Conclusion: This study points out that surgical abortion is not a contraceptive method. Most surgical abortions can be prevented by effective usage of modern contraceptive methods. The importance of well-planned contraceptive counseling and education is emphasized. Better family planning counseling and education, and the availability of modern contraceptive methods can easily decrease the incidence of surgical abortions.